Reversibility of nerve root sedimentation sign in lumbar spinal stenosis patients after decompression surgery - Barz, C.; Melloh, Markus; Staub, L.; Lord, S.; Merk, H.; Barz, T. (Springer, 2017)
© 2017 Springer-Verlag Berlin HeidelbergPurpose: The nerve root sedimentation sign (SedSign) is a magnetic resonance imaging (MRI) sign for the diagnosis of lumbar spinal stenosis (LSS). It is included in the assessment of LSS to help determine whether decompression surgery is indicated. Assessment of the reversibility of the SedSign after surgery may also have clinical implications for the decision about whether or not a secondary operation or revision is needed. This study investigated if lumbar decompression leads to a reversal of the SedSign in patients with LSS and a positive SedSign pre-operatively; and if a reversal is associated with more favourable clinical outcomes. If reversal of the SedSign is usual after sufficient decompression surgery, a new positive SedSign could be used as an indicator of new stenosis in previously operated patients. Methods: A prospective cohort study of 30 LSS patients with a positive pre-operative SedSign undergoing decompression surgery with or without instrumented fusion was undertaken to assess the presence of nerve root sedimentation (=negative SedSign) on MRI at 3 months post-operation. Functional limitation (Oswestry Disability Index, ODI), back and leg pain (Visual Analogue Scale, VAS), and treadmill walking distance were also compared pre- and 3 months post-operatively. The short follow-up period was chosen to exclude adjacent segment disease and the potential influence of surgical technique on clinical outcomes at longer follow-up times. Results: 30 patients [median age 73 years (interquartile range (IQR) 65–79), 16 males] showed a median pre-operative ODI of 66 (IQR 52–78), a median VAS of 8 (IQR 7–9), and a median walking distance of 0 m (IQR 0–100). Three months post-operation 27 patients had a negative SedSign. In this group, we found improved clinical outcomes at follow-up: median post-operative ODI of 21 (IQR 12–26), median VAS of 2 (IQR 2–4), and median walking distance of 1000 m (IQR 500–1000). These changes were all statistically significant (p < 0.001). Three patients had a positive SedSign at 3-month follow-up due to epidural fat (n = 2) or a dural cyst following an intra-operative dural tear (n = 1), but also showed improvements in clinical outcomes for ODI, VAS and walking distance. Conclusion: The reversibility of a pre-operative positive SedSign was demonstrated after decompression of the affected segmental level and associated with an improved clinical outcome. A persisting positive SedSign could be the result of incomplete decompression or surgical complications. A new positive SedSign after sufficient decompression surgery could be used as an indicator of new stenosis in previously operated patients.